Proving Al-Maqrizi’s Concept of the Determinants of Inflation: Cross Border Analysis - Nashr Akbar; Abdul Wahid al Faizin (Bank Indonesia, 2019)
This research discusses the determinants of inflation according to Al-Maqrizi, one of Ibnu Khaldun’s disciples. He argued that inflation is caused by natural and human error factors; the latter include government corruption and the excess supply of non-metal money. This study conducts a critical review of the work of al-Maqrizi, ighatsatul ummah bi kasyfil ghummah, supported by a panel data regression of cross-country data related to rates of inflation, rates of corruption and the number of natural disasters. The empirical data show that the rate of inflation is positively related to human error factors: corruption, tax and money supply. The results indicate the relevance of al-Maqirizi’s postulates to the modern day economy. However, natural disasters are not proven to be a significant factor for inflation at the country level. This paper contributes to the importance of the study of classical Muslim scholars’ thinking in order to understand current economic problems and ways of solving them.